Study on Statistical Damage Theory Model of Tailings in a Metal Ore under the Action of Moisture Absorption and Dehumidification Circulation. (15th October 2020) - Cao, Bing; Wei, Hua; Dou, Mei-Qi; Hu, Lin; Guo, Yao-hui
Abstract : In order to explore the variation law of mechanical properties of tailing sand of a metal ore in Hunan Province under the action of moisture absorption and dehumidification circulation, based on the indoor triaxial test results of tailing sand, this paper introduces the statistical damage theory, combined with the physical and mechanical properties of tailing sand, and studies the elastic-plastic mechanical properties of tailing sand on the basis of the Lemaitre strain equivalent theory. Giving full consideration of the change of tailing sand's pore and volume in the deformation process, an improved statistical damage constitutive model is proposed; it can reflect that the residual strength of tailings after the peak value still has bearing capacity under the action of dry wet circulation. Compared with the results of indoor triaxial consolidation undrained test, this constitutive model is more reliable.